Longitudinal Comparison of Patient-Level Outcomes and Costs Across Prostate Cancer Treatments With Urinary Problems. Issue 2 (March 2019) - Tang, Jun; Zhong, Lixian; Paoli, Carly; Paciorek, Alan; Carroll, Peter; Wilson, Leslie
Prostate cancer (PCa) is the leading cancer in men in the United States. This study evaluated direct costs of treating urinary problems after PCa treatments and determined predictors of long-term costs for urinary problems. Data from the Cancer of Prostate Strategic Urologic Research Endeavor registry was analyzed for this study. Annual treatment costs for urinary problems for up to 14 years were compared among different primary PCa treatments, which included radical prostatectomy, external beam radiation therapy, brachytherapy, and watchful waiting. A multivariate generalized estimating equation (GEE) model with bootstrapping was estimated to identify the predictors associated with treatment costs for urinary problems. A total of 3, 062 eligible patients were identified with a mean age of 65 years at diagnosis. Mean annual treatment cost for urinary problems across all patients with PCa was $118/patient. Those greater than 74 years old had the highest cost ($238/patient). Mean annual cost for urinary problems among only those with urinary problems was $432. Multivariate regression showed patients undergoing radical prostatectomy had significantly lower (−63%, p = .01) costs for urinary problems than those treated with watchful waiting. This study helps to understand the importance of treating urinary problems associated with different PCa treatments and highlights their medical care costs. The pattern of treatment costs for urinary problems across all PCa treatments suggests that clinicians need to offer treatment for urinary problems to all PCa patients over longer time periods, even to those choosing watchful waiting.